Dessiner son parcours professionnel, pour en tirer des enseignements - Pascale Corten-Gualtieri; Sylvie Dony; Evelyne d’Hoop (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
A recent visual creative activity carried out during a continuous education programme for teachers in higher education enhances reflective practice regarding professional development. Teachers were asked to draw their professional path as they would draw a route map. On the basis of this drawing, they were able to highlight the levers and obstacles in their professional development and then clarify their perspectives in terms of professional growth. This analysis was emphasized using a theoretical framework and exchanges in teams of two. All activities comprised an effective and stimulating preparation for writing a portfolio in which the teachers analyzed their professional practices and development. This article describes the theoretical framework and methods used during these activities; it then analyzes the results obtained based on the study of the various drawings made by the teachers and on an evaluation survey.